Antihypertensive, antidiabetic, and antioxidant properties of novel Azolla pinnata fern protein hydrolysates: inhibition mechanism, stability, profiling, and molecular docking - Qoms, Mohammed S.; Arulrajah, Brisha; Wan Ibadullah, Wan Zunairah; Ramli, Nurul Shazini; Shamsudin, Rosnah; Chau, De Ming; Saari, Nazamid (Springer, 2024)
The Azolla pinnata fern protein was enzymatically hydrolysed with Alcalase, Flavourzyme, and Papain at varying degrees of hydrolysis (10, 20, and 30%) to generate multi-biologically active protein hydrolysates. The extensively hydrolysed (30%) Alcalase-generated hydrolysate (AFPH-AE) was most active demonstrating antihypertensive (ACE inhibition), antidiabetic (DPP-IV, α-glucosidase, and α-amylase inhibition), and antioxidant (DPPH, ABTS, and FRAP) activities. AFPH-AE exhibited an uncompetitive inhibition mode against ACE and α-glucosidase, a mixed inhibition mode against α-amylase, and a noncompetitive inhibition mode against DPP-IV. This hydrolysate was highly stable under different food processing conditions including pH 5, 7, and 8, NaCl up to 150 mM, and a high temperature of 100 °C. The low molecular weight fraction (< 3 kDa) exhibited high biological activities, and a total of 15 low molecular weight bioactive peptides were identified. Molecular docking revealed that the peptide-enzyme interactions were mainly mediated via hydrogen bonds and hydrophobic interactions. Overall, these findings reveal the potential of AFPH-AE as a functional and/or nutraceutical ingredient with multifunctional antihypertensive, antidiabetic, and antioxidant effects.